Comparative histology of human and cow, goat and sheep liver. - Madhan KE; Raju S (Department of Surgery, UKM Medical Centre, 2014)
Comparative histology deals with the comparison of microscopic structural relations of the various animals with in the ecosystem. Here, we compare the microscopic structure of the human liver with domestic animals like cow, sheep and goat. Human and cow, goat and sheep’s liver were taken and divided in to 3 groups. We kept liver specimen in formalin for fixation. Thin cut sections of specimen were taken after paraffin embedding. Slides were stained by Haematoxylene and Eosin, later observed the histological features under light microscope. The study was undertaken to compare the histological differences like hepatic lobule, connective tissue septa, portal triad, hepatocytes of liver between human and cow, goat and sheep. It plays a useful tool for morphological studies based on the evolution. Hepatic lobule was hexagonal in shape in cow, goat and sheep, but it was not clearly seen in human liver. Hepatocytes were larger in human beings but smaller and polygonal in cow, goat and sheep. Connective tissue septa were scanty in human liver, in comparison to other animals. Central vein was closer to the hepatic lobule in human and goat’s liver, while in case of cow and sheep, it was found to be close to the portal triad. This comparative histological study may be useful to all the research scholars who undertaken similar studies, veterinary scientists and the field of liver transplantation.